2020
DOI: 10.1016/j.gca.2020.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The composition of Mars

Abstract: Comparing compositional models of the terrestrial planets provides insights into physicochemical processes that produced planet-scale similarities and differences. The widely accepted compositional model for Mars assumes Mn and more refractory elements are in CI chondrite proportions in the planet, including Fe, Mg, and Si, which along with O make up >90% the mass of Mars. However, recent improvements in our understandings on the composition of the solar photosphere and meteorites challenge the use of CI chond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
157
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(165 citation statements)
references
References 197 publications
(334 reference statements)
7
157
1
Order By: Relevance
“…To recover the deeper seismic discontinuities in Mars, we examined low‐frequency filtered autocorrelograms which show reflection signals at times consistent for the Martian olivine‐wadsleyite transition and the Martian core‐mantle boundary. Using different velocity models simulated for various compositional and thermal models (Khan et al, 2018; Panning et al, 2017; Yoshizaki & McDonough, 2020), the olivine‐wadsleyite transition and core‐mantle boundary of Mars would be at 1,110–1,170 and 1,520–1,600 km, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To recover the deeper seismic discontinuities in Mars, we examined low‐frequency filtered autocorrelograms which show reflection signals at times consistent for the Martian olivine‐wadsleyite transition and the Martian core‐mantle boundary. Using different velocity models simulated for various compositional and thermal models (Khan et al, 2018; Panning et al, 2017; Yoshizaki & McDonough, 2020), the olivine‐wadsleyite transition and core‐mantle boundary of Mars would be at 1,110–1,170 and 1,520–1,600 km, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…That lower-frequency signals from deep within Mars are observable is not too surprising, as Mars is a cold, dry planet, and seismic attenuation is strongly dependent on temperature and on the fluid content of rocks. We use four P wave velocity models (Figure 3b) to depth convert the stacked autocorrelograms, one is the LFAK model (Khan et al, 2018), three are from theoretical calculation of shear wave velocity for various bulk composition and thermal state models (Panning et al, 2017) where we assume a Vp/Vs ratio of 1.82 (Sohl & Spohn, 1997), and one is from a theoretical calculation of Vp (Yoshizaki & McDonough, 2020). Figure 3c shows the depth conversion of the reflectivity series filtered between 0.05 and 0.1 Hz using the four models shown in Figure 3b.…”
Section: Deeper Interior: Olivine-wadsleyite Transition and Core-mantmentioning
confidence: 99%
“…According to this study, the martian core contains light elements with ≤7 wt.% of S, less than previously suggested (Stewart et al, 2007), but contains O (5.2 wt.%) and H (0.9 wt.%) (Yoshizaki & Mc-Donough, 2020). The martian mantle is more oxidized and has a lower Mg# (= molar MgO/[MgO + FeO]) of ∼0.79 than the Earth's mantle (McDonough & Sun, 1995;Yoshizaki & McDonough, 2020).…”
Section: Mars Bulk Silicate Compositionmentioning
confidence: 99%
“…Previous studies also suggested that variation in Mg# [molar 100 × MgO/(MgO + FeO)], though subordinate to alkali variations at lower pressures, can affect the solidus temperature significantly (Herzberg et al, ; Hirschmann, ) at higher pressures as the effect of alkali diminishes because of enhanced compatibility of Na in clinopyroxene. Although all available models from geochemical and geophysical perspectives suggest that Martian mantle has either higher or similar total alkali concentration and much lower Mg# (~75–80) compared to the Earth's mantle (Mg#~90, McDonough & Sun, ; Workman & Hart, ), the Mg# and total alkali (Na 2 O+ K 2 O) concentration among different model Martian mantle compositions vary between 72 and 80 and 0.5 and 1.2 wt.%, respectively (Dreibus & Wanke, ; Khan et al, ; Khan & Connolly, ; Lodders & Fegley, ; Morgan & Anders, ; Ohtani & Kamaya, ; Sanloup et al, ;Taylor, ; Yoshizaki & McDonough, ). Among all the model composition, Dreibus and Wanke (DW) composition is the most widely accepted model for Martian bulk composition because it is derived from elemental correlations in Martian meteorites (Taylor, ).…”
Section: Introductionmentioning
confidence: 99%